HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAK TAKRAW PADA TIM SEPAK TAKRAW SMAN 01 KUANTAN HILIR - Satria Eka Lisdana; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is a relationship the between eye coordination and legs with skill sepak sila of game on sepak takraw team sepak takraw SMAN 01 Kuantan Hilir . The forms of this research are the correlation study, the population in this team from the team sepak takraw SMAN 01 kuantan Hilir, and the sample in this study is the team sepak takraw SMAN 01 Kuantan Hilir. which have numbered 15 people. Data taken in this study is a first-hand data and obtained from samples that have been set, namely in the form of numbers - the numbers of test results-eye coordination feet and test the ability to perform basic technique football precepts for 1 minute, with some categories of ratings on team sepaktakraw SMAN 01 Kuantan Hilir From the first analysis calculations relationship of X and Y, where rtab at significant level α (0,05) = 0.646 means r arithmetic (0,646)> rtab (0,532), which means that the hypothesis is accepted and there is a significant relationship the between eye coordination and legs with skills sepak sila Games Sepak Takraw in team sepaktakraw SMAN 01 Kuantan Hilir, then it can be concluded that the relationship the between the X and Y or eye and foot coordination relationship with skill sepak sila is significant. Thus the skills sepaksila team sepak takraw team SMAN 01 Kuantan Hilir in the forecast with their foot-eye coordination.Keywords: cooordination, sepak takraw